INTERSECTIONALITY OF RACE AND GENDER IN â€œHARRY POTTER: THE DEATHLY HALLOWSâ€ - Mira Utami (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
The term â€œintersectionalityâ€ appears back in the day of oppressing still incurred upon black women, the condition that has been spoken up for hundreds of year but never come to an end. KimberlÃ© Crenshaw as an advocate of American civil right for black women is voicing her thought regarding the intersection of race and gender from the clashes in treatment upon black women among the society. The theory of intersectionality questions the power of black women that is in bare minimum, likely none, in opposite to the power of white men as the highest in the society. Thus, the theory is used to analyze the intersections of human being in the term of race, gender, and sex as well.This research found the intersectionality of race and gender from the perspective of Crenshaw over the characters in the novel â€œHarry Potter and The Deathly Hallowsâ€ written by J.K. Rowling. The findings show the intersections of human and non-human creatures appeared in the novel along the terms of wizarding world of Harry Potter.